Pengaruh Model Penemuan Terbimbing (Guided Discovery) Terhadap Kemampuan Penalaran Matematis Siswa Pada Materi Bilangan di MTS Al-Khairiyah Pontang Kelas VII - Jaka Wijaya Kusuma; Maulida Nur; Eva Cahya Ningsih (Departement of Mathematics Education, 2023)
This research is motivated by the cause of the low mathematical reasoning ability of students, namely because the mathematics learning method used by most teachers is still using the traditional approach. Based on some of these problems, it can be said that mathematical reasoning ability is an important part that must be developed and possessed by students. One way to develop it is by applying a guided discovery model in learning mathematics. The aims of this study are 1) To find out whether students' mathematical reasoning abilities with the guided discovery model are better than the conventional model. 2) To find out how the influence of the guided discovery model on students' mathematical reasoning abilities. This study uses quantitative methods with experiments. The subjects of this study were 40 students consisting of 20 experimental class students and 20 control class students in class VII students. The data collection techniques in this study were in the form of tests. The results of the study revealed that 1) The mathematical reasoning ability of students who used the guided discovery model was better than using the conventional method, the average difference was 0.8. 2) Based on the results of Cohen's d obtained with the value of Tw = 1.14 and Tsw = 0.80 with a significance level of 5% (TW > Tsw). So the effect size of this analysis includes criteria that are classified as high. Thus, the conclusions of this study are: 1) The students' mathematical reasoning ability with the guided discovery model is better than the conventional model. 2) The guided discovery model has an influence on the students' mathematical reasoning ability is classified as high.